Single-Leg Balance and Lower Limb Strength: Quantitative Analysis with the Balance Master System - José Manuel Delfa-de-la-Morena; Pedro Pinheiro Paes; Débora Priscila Lima de Oliveira; Frederico Camarotti Júnior; Bruna Daniele Monteiro Lima; Miriam García-González; Juan-José Mijarra-Murillo; Víctor Riquelme-Aguado (Journal of Functional Morphology and Kinesiology)
Objective: This study investigates the relationship between lower limb strength and postural stability in single-leg stance using the Balance Master system. Methods: The research involved 64 participants divided into sedentary and physically active groups based on metabolic equivalents of task (METs) values, normal weight, overweight, and obese according to body composition. Postural control was evaluated using the Sensory Organization Test. Results: The results showed that there were no significant differences in mean and maximum lower limb strength between the groups. Furthermore, postural stability in open and closed eyes conditions did not show significant differences between the groups. However, a significant positive correlation was observed between lower limb strength and stability in single-leg stance with eyes open. Conclusions: These findings suggest that lower limb muscle strength is essential for postural stability, especially when vision is available to aid balance. The study highlights the importance of interventions focused on strengthening muscles to improve physical functionality in adults.